A brief review of surface-functionalized cotton fabrics. Issue 3 (1st September 2013) - Gigli, Giuseppe; Ingo, Gabriel M.; Padeletti, Giuseppina; Caschera, Daniela; Cortese, Barbara
Abstract : Surface modification of textiles with desired functionalities can be engineered by a considerable number of techniques ranging from traditional treatments to multifunctional approaches. Textiles, in fact, offer a challenging platform for functional modifications in order to meet additional strategic requirements for a large variety of applications. This article reviews recent developments involving modification of cotton textiles using physical methods (corona discharge, plasma) and chemical methods (vapor-phase atomic layer deposition treatment, surface grafting, enzymatic modification, cationic modification with nanoparticles, sol-gel technique, method and treatment with different reagents) and their characterization. The authors will present how the controlled wettability has been integrated into traditional materials to improve their performances and to extend their practical applications by developing new functionalities. The authors give a brief background on applications of cotton-modified surfaces and the development of novel innovative production techniques used to modify the surface materials and to improve the product quality.